Transformative Islamic Religious Education Model for Muslim Student Minorities at Madrasah Aliyah in Bali - Abu Bakar; Angga Teguh Prastyo; A’dawiyah binti Ismail; Muh. Syamsul Arifin; Isna Nurul Inayati; Ulya Himmatin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The transformative Islamic religious education model for Muslim minorities in Bali plays a strategic role in fostering social harmony within a multicultural society. However, studies on Islamic education in Indonesia have predominantly focused on Muslim-majority contexts, leaving limited attention to how Islamic education functions within Muslim minority communities. This gap necessitates a deeper exploration of educational models that enable Muslims to sustain their faith while engaging harmoniously in plural societies. Muslim minorities in Bali live in a complex religious environment, thus requiring an educational approach that not only focuses on the transfer of religious knowledge but also emphasizes the development of tolerant, inclusive, and adaptive attitudes. This study aims to analyze the implementation of the transformative Islamic education model at MA Khalifa Nusantara Denpasar as a means of strengthening Islamic identity while maintaining harmony with the Hindu majority community. The research employed a qualitative approach with a descriptive-analytical method. Data were collected through in-depth interviews with teachers and students, observation of learning activities, and literature review related to Islamic education and Muslim minorities. Content analysis was conducted to identify key themes, while data validity was ensured through source triangulation. The findings reveal that teachers serve as the main actors in implementing transformative education. They act not only as instructors but also as role models of patience, sincerity, creativity, and emotional management. The madrasah also fosters learning communities that promote solidarity, collective spirit, and spaces for interreligious dialogue. As a result, Muslim minority students develop pride in their Islamic identity while maintaining harmonious relationships with non-Muslim peers. This study affirms that transformative Islamic education contributes to shaping a generation of Muslim minorities who are religious, tolerant, and globally competitive.